Determination of Motivation and Performance: Analysis of Job Satisfaction, Employee Engagement and Leadership - Primadi Candra Susanto; Siera Syailendra; Ryan Firdiansyah Suryawan (International Journal of Business and Applied Economics, 2023)
This article aims to review and synthesize a literature review related to employee performance, motivation, job satisfaction, employee engagement, and leadership and to see the research results of the variables that will be reviewed and whether there is an influence between one variable and another. This study uses a literature review by looking for references related to related variables. This study provides an overview of the articles obtained by describing the influence between variables. The results of the study show that several variables influence the evidence of exposure in a matrix. The employee performance study in this literature review article explicitly focuses on supporting variables that can improve employee performance, namely motivation, job satisfaction, employee engagement, and leadership.